PENERAPAN METODE HIRA SEBAGAI UPAYA MENGURANGI RISIKO KECELAKAAN KERJA DAN PENYAKIT AKIBAT KERJA DI BENGKEL LAS PT.BANGUNCIPTA PERSADA MANDIRI - Tarigan, Umar Abdul Gani; Dur, Sajaratud; Aprilia, Rima (Math Educa Journal, 2023)
The actions of workers and the conditions of the work place greatly influence the occurrence of work accidents, where accidents that often occur in welding workshops are workers tripping over tools or materials in the welding area, ringing in their ears, inhaling welding fumes, hands being pinched, being hit by hot iron sparks, and so on. Data collection is carried out by direct interviews in order to obtain data from work processes, accidents that may occur and findings from direct observations and similar related research. In processing the data, after the analysis has been carried out, it can be calculated based on the level of risk in the form of a value. This research aims to reduce the risk of work accidents using the Hazard Identification and Risk Assessment method, where this method is to find out how to identify potential dangers that may arise in the area and assess the risks using a risk assessment matrix. In this research, qualitative analysis was carried out using an observational approach. Of the 7 workshop activities, namely dropping goods/materials using a crane, cutting materials, welding, plate rolling, smoothing weld marks (granding), sandblasting, and painting, there are 28 potential hazards which are classified into: 21 risks in the Low Risk category (75%), 3 risks in the Moderate category (11%), and 4 risks in the High category (14%). With a frequency level range of 1-5, the severity value range starts from 1-2 and the risk levels obtained are low, moderate and high.